Solving the all-FLR ICRH integro-differential wave equation as a high-order differential equation for studying combined ICRH-NBI heating. (4th December 2020) - Van Eester, Dirk; Lerche, E A
Abstract: A fast and intuitive method is proposed to solve the integro-differential wave equation relevant for modelling ion cyclotron resonance heating (ICRH) at any cyclotron harmonic, for arbitrary ion distributions and retaining all finite Larmor radius effects. The method is inspired on recent work of Budé who proposed to fit the dielectric tensor in k -space by a higher order polynomial, allowing to derive a suitable differential operator that conveniently mimics the integro-differential operator in a sufficiently large k ⃗ -range to describe all physically relevant wave modes in k ⃗ -space. Eliminating a drawback of the Budé method by going back to first principles yields a wave equation dielectric response operator that guarantees a positive definite power absorption for populations in thermal equilibrium—as physically expected—and that can directly be used in the Fokker–Planck equation. The method is exploited for 1D application but retaining the toroidal curvature. Analytical expressions of the components of the dielectric tensor are available for Maxwellian distributions as well as bi-Maxwellians with a finite parallel drift. Numerical integration of the velocity space integrals allows to account for arbitrary distributions. A number of examples relevant for high performance tokamak plasma operation and exploiting simultaneous ICRH and neutral beam injection heating are given to illustrate the method's potential.